Developing a lung nodule management protocol specifically for cardiac CT: Methodology in the DISCHARGE trial. (2020) - Haase, Robert; Dodd, Jonathan D.; Kauczor, Hans-Ulrich; Kazerooni, Ella A.; Dewey, Marc
Highlights: No lung nodule management algorithm exists specifically for cardiac CT. The DISCHARGE trial is a pragmatic prospective randomized trial currently being undertaken across 16 countries in Europe for patients with stable chest pain. As part of the trial a lung nodule algorithm is being evaluated based on modified lung-RADS nodule management algorithms. The methodology of this 'Lung-RADS for cardiac CT' algorithm is presented. Abstract: Purpose: In this methodology paper we describe the development of a lung nodule management algorithm specifically for patients undergoing cardiac CT. Methods: We modified the Lung-RADS algorithm specifically to manage lung nodules incidentally detected on cardiac CT (Lung-RADS for cardiac CT). We will evaluate the modified algorithm as part of the DISCHARGE trial (www.dischargetrial.eu ) in which patients with suspected coronary artery disease are randomly assigned to cardiac CT or invasive coronary angiography across Europe at 16 sites involving 3546 patients. Patients will be followed for up to four years. Results: The major adjustments to Lung-RADS specifically for cardiac CT relate to 1) incomplete coverage of the lungs by cardiac CT compared with chest CT, and when to order a completion chest CT versus a follow up chest CT, 2) cardiac CT findings will not trigger annual lung-cancer screening, and 3) a lower threshold of at least 10 mm for classifying new ground glass nodules as probably benign (category 3). Conclusions: The DISCHARGE trial will assess a lung nodule management algorithm designed specifically for cardiac CT in patients with stable chest pain across Europe.